Tren Penerbitan Mushaf dalam Komodifikasi Al-Qur’an di Indonesia - Eva Nugraha (Ulumuna, 2014)
As a sacred thing, muṣḥaf of the Qur’an has long been the commoditized objects. In Indonesia, it has been published and circulated into markets with its various forms since 150 years ago. However, in the last ten years, the publication of the Qur’an has changed dramatically in terms of shape, form, content and theme. This article seeks to examine how publishers manage their product of printed Qur’an and promote them in market. It shows that publishers have responded the demands of market to the printed al-Qur’an by means of increasing the quality of the printed material of the scripture and framing the product in accordance with the trend of the market.